Theory of Mind Deficits and Social Emotional Functioning in Preschoolers with Specific Language Impairment - Vissers, Constance; Koolen, Sophieke (Frontiers in Psychology, 2016)
Children with Specific Language Impairment (SLI) often experience emotional and social difficulties. In general, problems in social emotional functioning can be cognitively explained in terms of Theory of Mind (ToM). In this mini-review, an overview is provided of studies on social-emotional functioning and ToM in preschoolers (average age from 2.3 to 6.2 years) with SLI. It is concluded that, similar to school-aged children with SLI, preschoolers with SLI have several social-emotional problems and that both cognitive and affective aspects of ToM are impaired in those children. Based hereon, three possible causal models for the interrelation between language, ToM and social emotional functioning are put forward. It is proposed that future research on the construct and measurement of early ToM, social emotional functioning and language development in preschoolers with SLI is needed to achieve early detection, tailored treatment, and ultimately insight into the pathogenesis of SLI.